Comparisons on isomeric 1, 10-phenanthroline aromatic heterocyclic derivatives with triphenylamine and thiophene donors before and after rhenium(I) carbonyl complexation. Issue 24 (16th June 2016) - Peng, Yu-Xin; Xu, Dan; Wang, Na; Tao, Tao; Hu, Bin; Huang, Wei
Abstract: We have described herein a series of unsymmetric 1, 10-phenanthroline (phen) based aromatic heterocyclic derivatives with triphenylamine (TPA) and thiophene donors (L1 –L5 ) and their respective neutral tricarbonyl rhenium(I) complexes (6a –6e ). Comparisons between isomeric compoundsL1 /L2 and6a /6b as well asL3 /L4 /L5 and6c /6d /6e have been made on their 1 H NMR and UV/Vis spectra, single-crystal structures and density function theory (DFT) calculations. The alterations of conjugated system of the whole molecules, originating from the introduction of 2-, 3- or 3, 8-substituted TPA and thiophene groups of phen, are responsible for the structural and spectral discrepancy of these structural isomers. In particular, the introduction of TPA and/or thiophene donors at 2-postion of phen (L1 andL3 ) leads to smaller band gaps than their respective 3-substituted isomers (L2 andL4 ). In addition, rhenium(I) ion complexation could slightly lower the highest occupied molecular orbital (HOMO) energy levels but significantly decrease the lowest unoccupied molecular orbital (LUMO) energy levels of the molecular system. Graphical abstract: Comparisons between asymmetric and isomeric phen based compounds with 2-, 3- or 3, 8-substituted TPA and thiophene donors and their respective tricarbonyl Re(I) complexes have been made on their 1 H NMR and UV/Vis spectra, single-crystal structures and DFT calculations, where the alterations of conjugated system and steric hindrance before and after Re(I) ion complexation are responsible for the structural and spectral discrepancy.